2021
DOI: 10.31004/obsesi.v6i3.1794
|View full text |Cite
|
Sign up to set email alerts
|

Parenting Pattern in Instilling The Character for Children From an Early Age

Abstract: The educational process starts from the family, so that the family becomes a good place to teach moral values and good character education. This research is aimed at knowing the parental roles in developing the children’s character since early age in Bakung Ilir Gedong Meneng. The reseasrch used qualitative method with fenomenology method which focused on natural paradigm based on the fenomenolgy point of view. The research findings shows that the caring model of families in inplanting the charachter to childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
2
0
2
Order By: Relevance
“…This is consistent with a study by Handayani 2021, which showed that the family is the cornerstone of society and is primarily responsible for the process of socialization [ 135 ]. Moreover, Suri's 2021 study demonstrated that the process of socialization carried out by parents should include introducing children to positive social values and their significance within society [ 136 ]. Additionally, Salmiati and Zaman's 2021 study emphasized that parents should support their children in engaging in human services [ 137 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with a study by Handayani 2021, which showed that the family is the cornerstone of society and is primarily responsible for the process of socialization [ 135 ]. Moreover, Suri's 2021 study demonstrated that the process of socialization carried out by parents should include introducing children to positive social values and their significance within society [ 136 ]. Additionally, Salmiati and Zaman's 2021 study emphasized that parents should support their children in engaging in human services [ 137 ].…”
Section: Discussionmentioning
confidence: 99%
“…Usia dini merupakan usia potensial untuk pembentukan karakter karena pertumbuhan dan perkembangan yang terjadi pada rentang usia tersebut akan menjadi fondasi bagi anak bagi masa depannya kelak. Oleh karenanya, masa tumbuh kembang anak pada usia 0-5 tahun disebut sebagai masa keemasan atau golden age (Saptatiningsih & Permana, 2019;Suri, 2021). Orang tua harus dapat melihat kesiapan anak untuk distimulasi agar memperoleh keterampilan dan pengetahuan baru sesuai dengan usia perkembangannya karena tumbuh dan kembang anak mengikuti pola yang sudah dapat diperkirakan dengan cara belajar dan kecepatan yang berbeda-beda.…”
Section: Hasil Dan Pembahasanunclassified
“…Keberhasilan orang tua dalam mendidik anak dipengaruhi oleh keterampilan pengasuhan yang dikembangkan oleh orang tua. Pengasuhan yang diterapkan orang tua pada anak akan berpengaruh terhadap peran orang tua dalam penanaman karakter yang meliputi kemampuan untuk mengenalkan, mengajarkan, membiasakan, dan menjadi teladan (Suri, 2021).…”
Section: Pendahuluanunclassified